Do alcoholic beverages interfere in the force of orthodontic elastics? - Matheus Melo PITHON; Jéssica Rocha BARRETTO; Camilla Souza Santos ANDRADE; Fernando Pereira de NOVAES; Murilo de Novaes LUZ; Ana Carolina Dias Viana de ANDRADE; Raildo da Silva COQUEIRO
Objective: To evaluate the effects of different alcoholic beverages on the decline in force of orthodontic elastics. Material and method: In a laboratory study, 6 groups of alcoholic beverages were tested. Control group (Group 1) was composed of distilled water. Experimental groups were Whisky (Group 2), Brandy (Group 3), Vodka (Group 4), Beer (Group 5), Sugar Cane Spirit/Rum (Group 6), Wine (Group 7). In the experimental groups, templates were used to enable elastics to be submerged in the alcoholic beverages for 30 seconds once a day. Force was measured with a digital dynamometer in six different time intervals: baseline, 1, 7, 14, 21 and 28 days. Result: There were no significant differences between the treatments in the time intervals: baseline, 7, 14 and 28 days. There were statistical differences between Group 7 and the others in the first 24 hours, and between Group 1 and the others after 21 days. After 28 days, there were no significant differences in the force pattern among all groups (p<0.05). Conclusion: Alcoholic beverages had no influence on the decline in force of the chain elastics.